Implications of Oxidative Stress and Potential Role of Mitochondrial Dysfunction in COVID-19: Therapeutic Effects of Vitamin D - Natalia de las Heras; Virna Margarita Martín Giménez; León Ferder; Walter Manucha; Vicente Lahera (MDPI AG, 2020)
Due to its high degree of contagiousness and like almost no other virus, SARS-CoV-2 has put the health of the world population on alert. COVID-19 can provoke an acute inflammatory process and uncontrolled oxidative stress, which predisposes one to respiratory syndrome, and in the worst case, death. Recent evidence suggests the mechanistic role of mitochondria and vitamin D in the development of COVID-19. Indeed, mitochondrial dynamics contribute to the maintenance of cellular homeostasis, and its uncoupling involves pathological situations. SARS-CoV-2 infection is associated with altered mitochondrial dynamics with consequent oxidative stress, pro-inflammatory state, cytokine production, and cell death. Furthermore, vitamin D deficiency seems to be associated with increased COVID-19 risk. In contrast, vitamin D can normalize mitochondrial dynamics, which would improve oxidative stress, pro-inflammatory state, and cytokine production. Furthermore, vitamin D reduces renin-angiotensin-aldosterone system activation and, consequently, decreases ROS generation and improves the prognosis of SARS-CoV-2 infection. Thus, the purpose of this review is to deepen the knowledge about the role of mitochondria and vitamin D directly involved in the regulation of oxidative stress and the inflammatory state in SARS-CoV-2 infection. As future prospects, evidence suggests enhancing the vitamin D levels of the world population, especially of those individuals with additional risk factors that predispose to the lethal consequences of SARS-CoV-2 infection.